PENGARUH PENGETAHUAN KEUANGAN, SIKAP KEUANGAN, INKLUSI KEUANGAN DAN FINANCIAL TECHNOLOGY TERHADAP PERSONAL FINANCE UMKM DI MADURA - Siti Sundari; Moh. Zaki Kurniawan; Bambang Sudarsono (Fakultas Ekonomi Universitas Kadiri, 2024)
This study aims to identify the impact of financial knowledge, financial attitudes, financial inclusion, and Financial Technology on Personal Finance in Micro, Small and Medium Enterprises (MSMEs) in the Madura region. The subject of this study is MSME actors in Madura. As many as 100 MSME actors in Madura became respondents in this study through the distribution of questionnaires. The method used in this research is purposive sampling. The results of the study indicate that there is a positive impact of financial attitudes on the personal finance of MSMEs in Madura. However, financial knowledge, financial inclusion, and financial technology did not have a significant impact on MSME personal finance in Madura.